Analysis of the Application of the Islamic Economic System in KSP Tunas Artha Mandiri Syariah Malang City in Empowering Micro Small and Medium Enterprises (MSMEs) - Agustini, Herlini; Saqina, Rizkanira; Anastasya, Kerin; Kholm, Masiyah (Yayasan Rahmat Islamiyah, 2025)
This study aims to analyze the application of the Islamic economic system to MSMEs with a case study of KSP Tunas Artha Mandiri Syariah in Malang City. The research method used is a qualitative descriptive approach with data collection techniques through interviews, observations, and literature studies. The results of the study indicate that Islamic economic principles, such as mudharabah, musyarakah, and without usury elements, have been applied in the financing scheme at KSP Tunas Artha Mandiri Syariah. The implementation of this system provides benefits for MSME actors, especially in terms of access to financing and increasing business sustainability, although there are still obstacles such as a lack of understanding of the concept of Islamic economics and limited resources. In conclusion, the application of the Islamic economic system at KSP TAM Syariah has proven to be able to significantly encourage MSME empowerment through a fair, transparent, and sharia-based financing system, as well as being an alternative solution for business actors who want to avoid usury practices.